The role of social support toward internet addiction on high school students - Lulu’ul Jannah (Indonesian Institute for Counseling, Education and Theraphy, 2024)
During the pandemic cases of internet addiction increased. Advanced internet usage because of all sectors turned online that can increase risk of developing internet addiction. One of the important protective factors against internet addiction in crisis situations is social support. The aim of this study is to examine the role of social support from parents, teachers, and peers on internet addiction among high school/equivalent students. A survey toward 208 high school/equivalent students in Yogyakarta was conducted and showed that only peer social support has negatively significant predicted internet addiction which is equal to 5,3%, while social support from parents and teachers not significant. This study contributes to predicting protective factor of internet addiction from social support source’s view.